Maternal Imprisonment and Family Life : From the Caregiver's Perspective - Booth, Natalie (Book collections on Project MUSE., 2020)
Exploring the untold experiences of family members and friends caring for the children of female prisoners in England and Wales, this book analyses the complex challenges of the 'family sentence' they serve and the realities of their disenfranchised status in society, policy and practice.